2015
DOI: 10.1002/cam4.490
|View full text |Cite
|
Sign up to set email alerts
|

Association of BMI with overall survival in patients with mCRC who received chemotherapy versus EGFR and VEGF‐targeted therapies

Abstract: Although a raised body mass index (BMI) is associated with increased risk of colorectal cancer (CRC) and recurrence after adjuvant treatment, data in the metastatic setting is limited. We compared overall survival (OS) across BMI groups for metastatic CRC, and specifically examined the effect of BMI within the group of patients treated with targeted therapies (TT). Retrospective data were obtained from the South Australian Registry for mCRC from February 2006 to October 2012. The BMI at first treatment was gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 25 publications
0
23
1
Order By: Relevance
“…It seems that correlation between cancer and BMI is far to be linear because not all obese patients might eventually develop colorectal cancer. However, a recent report highlights BMI as an independent predictor for overall survival dealing with overweight and obese patients with mCRC treated with Bevacizumab [ 181 ]. Additionally, the association of obesity with survival of CRC patients is likely to be affected by the timing of BMI measurement [ 182 ].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that correlation between cancer and BMI is far to be linear because not all obese patients might eventually develop colorectal cancer. However, a recent report highlights BMI as an independent predictor for overall survival dealing with overweight and obese patients with mCRC treated with Bevacizumab [ 181 ]. Additionally, the association of obesity with survival of CRC patients is likely to be affected by the timing of BMI measurement [ 182 ].…”
Section: Discussionmentioning
confidence: 99%
“…showed that high BMI values and large visceral fat content were associated with poorer response, shorter time-to-progression and shorter overall survival in patients treated with bevacizumab and chemotherapy, but there was no significant association in patients treated with chemotherapy alone [ 180 ]. The negative impact of adiposity was supported by a study by Patel et al ., in which the authors concluded that overweight BMI represented an independent, poor prognostic indicator for survival in patients undergoing chemotherapy with and without targeted therapy [ 181 ]. Besides, in breast cancer, Crozier et al .…”
Section: Introductionmentioning
confidence: 99%
“…In another similar trial, the investigators compared OS across the BMI groups for CRC, and they found that the OS was shorter for patients who were underweight and overweight compared to normal in the group of patients receiving CT + targeted therapy. There was no difference in OS for CT alone [154]. In a recent multicentric study, we demonstrated that obesity serves as a prognostic factor for mCRC patients who have been treated with bevacizumab-based regimens.…”
Section: In Metastatic Diseasementioning
confidence: 59%
“…There are also other trials with contradictory results [151][152][153][154][155]. In a trial investigating the influence of BMI on outcomes in advanced CRC patients receiving chemotherapy with or without targeted therapy, BMI was shown as an independent prognostic factor for survival in patients receiving chemotherapy (CT), but not in patients receiving CT plus targeted therapy [151].…”
Section: In Metastatic Diseasementioning
confidence: 99%